Association of endoparasites and productivity of highland sheep in Ethiopia - Bekele, T.; Bruns, E.; Kasali, O.B.; Wolde-Mariam, W.A. (Elsevier, 1992)
Presents a study of endoparasite productivity in sheep carried out at Debre Berhan, Dejen, Tulu Meko and Wereilu in the Ethiopian highlands in 1988 and 1989. Determines the association between some indicators of endoparasitism with productivity. Presents data on the relative association of EPG and PCV on productivity traits, body weight, body condition score and the phenotypic and environmental correlations. Presents also the least-squares means of productivity traits and EPG counts for all sites by groups of PCThe least-squares means for productivity traits and the parameters for endoparasitism by fixed environmental and physiological factors for all sites is also given.